Size and Development of the Shadow Economy in Germany and Austria: Some preliminary findings - Friedrich Schneider (Center for Research in Economics, Management and the Arts (CREMA), 2007)
The size and development of the shadow economy of Germany and Austria is estimated, us-ing various estimation procedures. An increased burden of taxation and social security pay-ments, combined with intensive labor market regulation, quality of state institutions and the tax morale are the driving forces for the shadow economy. Moreover, the results of recent surveys for Germany and Austria demonstrate, that the readiness to undertake illicit employ-ment as well as its acceptance are high in both countries. Finally, conclusions are made about the effect of the shadow economy on the official one and incentive oriented policy means are presented, so that the ?black? value added can be transformed into official value added.
Keywords: O17; O5; D78; H2; H26; 330